Error Analysis on Student’s Final Project Paper Abstract - Vidhiasi, Dhion Meitreya (CV. Tripe Konsultan, 2024)
An abstract is a brief and all-encompassing synopsis of scientific literature. Abstracts facilitate readers’ comprehension of article contents concisely and expeditiously. Hence, it is imperative to craft the abstract in a captivating manner to pique the reader’s curiosity and encourage them to peruse the complete content. An effective abstract should be precise, objective, logically organised, easily understandable, and concise. Nevertheless, several individuals, namely those studying Nautical Sciences, have encountered difficulty when it comes to writing in English. The task becomes further intricate since it involves meeting all the requirements, such as structuring and presenting coherent concepts to ensure the reader’s understanding of the text. The objective of this study is to identify the flaws present in the final project abstract of the Nautical Sciences Student at Akademi Maritim Nusantara Cilacap. This study employs a qualitative methodology, utilising a descriptive analysis technique. A total of ten samples were deliberately gathered for this investigation in the year 2022. The research findings indicate that there are two major concerns regarding faults in composing the abstract, specifically those pertaining to clarity and grammatical accuracy. Clarity errors encompass issues related to brevity (21) and the utilisation of passive voice (15). In addition, the data contained six grammatical problems, specifically verb errors (21), punctuation errors (10), preposition errors (7), spelling errors (5), conjunction errors (5), and article errors (4).